Post-concussive Dizziness: A Review and Clinical Approach to the Patient - Gianoli, Gerard J. (Frontiers in Neurology, 2022)
Dizziness is a frequent complaint after head trauma. Among patients who suffer a concussion (mild traumatic brain injury or mTBI), dizziness is second only to headache in symptom frequency. The differential diagnosis of post-concussive dizziness (PCD) can be divided into non-vestibular, central vestibular and peripheral vestibular causes with growing recognition that patients frequently exhibit both central and peripheral findings on vestibular testing. Symptoms that traditionally have been ascribed to central vestibular dysfunction may be due to peripheral dysfunction. Further, our ability to test peripheral vestibular function has improved and has allowed us to identify peripheral disorders that in the past would have remained unnoticed. The importance of the identification of the peripheral component in PCD lies in our ability to remedy the peripheral vestibular component to a much greater extent than the central component. Unfortunately, many patients are not adequately evaluated for vestibular disorders until long after the onset of their symptoms. Among the diagnoses seen as causes for PCD are (1) Central vestibular disorders, (2) Benign Paroxysmal Positional Vertigo (BPPV), (3) Labyrinthine dehiscence/perilymph fistula syndrome, (4) labyrinthine concussion, (5) secondary endolymphatic hydrops, (6) Temporal bone fracture, and (7) Malingering (particularly when litigation is pending). These diagnoses are not mutually exclusive and PCD patients frequently exhibit a combination of these disorders. A review of the literature and a general approach to the patient with post-concussive dizziness will be detailed as well as a review of the above-mentioned diagnostic categories.